2013
DOI: 10.1371/journal.ppat.1003183
|View full text |Cite
|
Sign up to set email alerts
|

Poxvirus Targeting of E3 Ligase β-TrCP by Molecular Mimicry: A Mechanism to Inhibit NF-κB Activation and Promote Immune Evasion and Virulence

Abstract: The transcription factor NF-κB is essential for immune responses against pathogens and its activation requires the phosphorylation, ubiquitination and proteasomal degradation of IκBα. Here we describe an inhibitor of NF-κB from vaccinia virus that has a closely related counterpart in variola virus, the cause of smallpox, and mechanistic similarity with the HIV protein Vpu. Protein A49 blocks NF-κB activation by molecular mimicry and contains a motif conserved in IκBα which, in IκBα, is phosphorylated by IKKβ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
176
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(186 citation statements)
references
References 69 publications
7
176
0
Order By: Relevance
“…Comparable phosphodegron-like (PDL) motifs were found in viral proteins that target the NF-B pathway by interfering with the ␤-TrCP function. The Epstein-Barr virus (EBV) latent membrane protein 1 (LMP1) and the VACV A49 protein were shown to block the degradation of IB␣ by binding to ␤-TrCP (40,68). Mutagenesis analysis demonstrated that the PDL motifs of both proteins were required for i., the cells were incubated with 100 ng/ml RhTNF-␣ for the indicated times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparable phosphodegron-like (PDL) motifs were found in viral proteins that target the NF-B pathway by interfering with the ␤-TrCP function. The Epstein-Barr virus (EBV) latent membrane protein 1 (LMP1) and the VACV A49 protein were shown to block the degradation of IB␣ by binding to ␤-TrCP (40,68). Mutagenesis analysis demonstrated that the PDL motifs of both proteins were required for i., the cells were incubated with 100 ng/ml RhTNF-␣ for the indicated times.…”
Section: Discussionmentioning
confidence: 99%
“…The HA-␤-TrCP and FLAG-tagged vaccinia virus (VACV) A49 (FL-A49) expression plasmids were kindly provided by G. L. Smith (University of Cambridge, Cambridge, United Kingdom) and have been previously described (40). For the recombinant adenoviruses (Ad), we cloned SVV ORF61 from DNA isolated from TRFs infected with SVV.eGFP using the DNeasy blood and tissue kit (Qiagen) with the following primers: 5=-CACCGAATTCACCATGAACCCCCCGGCGTATA CC-3= (ORF61 FW) or 5=-CACCGAATTCACCATGGACTACAAGGAT GACGACGATAAGAACCCCCCGGCGTATAC-3= (ORF61 FW-FLAG) and 5=-AATAAAGGATCCTTATTTTCTCCGTACCTTTTTAGTTAAC ATTTCAATGCG-3= (ORF61 Rev).…”
Section: Methodsmentioning
confidence: 99%
“…VACV interacts with TLR2 (16) and TLR4 (17) and produces early direct or indirect viral inhibitors of the NFκB pathway such as A46 (18), A49 (19), A52 (18), B14 (20), C4 (21), E3 (22), K1 (23), K7 (24), M2 (25), and N1 (26). New York vaccinia virus (NYVAC), a highly attenuated VACV strain used as vaccine vector, lacks most of these proteins but encodes NFκB pathway Significance Although poxvirus vectors are widely used in preclinical and clinical trials as candidate vaccines for multiple pathogens, how these vectors affect the host immune response is not clear.…”
mentioning
confidence: 99%
“…This protein displays molecular mimicry since it contains a motif similar to that in IkBa that is phosphorylated by IKKb and subsequently binds to the E3 ligase b-TrCP. This allows A49 to preferentially bind b-TrCP and hence prevent it ubiquitylating IkBa [23]. Remarkably, although the VACV NFkB inhibitors described above would appear to be functioning redundantly, each inhibitor has been shown to contribute to virulence since viruses lacking just a single inhibitor are attenuated in vivo compared to wild type VACV [24].…”
Section: Direct Targeting Of Nfkb and Its Proximal Kinases By Poxvirusesmentioning
confidence: 99%